Erotism and the Translation of the Poetry "Di Antara Kita" by Ajip Rosidi and "Nyanyian Duniawi" by W.S. Rendra - Eka Ugi Sutikno (SUAR BETANG, 2023)
Undoubtedly W. S. Rendra's poem “Nyanyian Dunia” can be brought closer to semantics, worldviews, and humanities values. However, the three things above become a contrast when faced with research that focuses on eroticism and Newmark's method of translation. Mainly “Di Antara Kita” by Ajip Rosidi, which has not yet been analyzed. This study aims to explain how erotic texts are presented to create aesthetics in poetry writing and how the three poems above are translated through the perspective of the Newmark translation method. The method used in this article is qualitative. The results show that “Di Antara Kita” on ‘Between Us’ and “Nyanyian Duniawi” on ‘A Worldly Song’, translated by Harry Aveling above, is dominated by the free translation method, and the diction contained in the source text and translation cannot be classified into in pornographic texts. The conclusion is that eroticism in the two poems above is confronted with the choice of diction, so the poems “Di Antara Kita” and “Nyanyian Duniawi” are not included in pornography, which is so verbal and obscene. Also, the eroticism in the two poems above reflects the desire of the two subjects who want each other’s love and bodies. AbstrakTidak diragukan lagi, puisi W. S. Rendra yang berjudul “Nyanyian Dunia” memiliki nilai semantik, pandangan dunia, dan humaniora yang kental. Akan tetapi, ketiga hal itu menjadi kontras ketika dihadapkan pada penelitian yang menitikberatkan pada erotisme dan metode penerjemahan ala Newmark. Terlebih “Di Antara Kita” karya Ajip Rosidi yang belum pernah dianalisis. Tujuan kajian ini ialah menjelaskan bagaimana teks erotisme dihadirkan untuk menciptakan estetika dalam penulisan puisi dan bagaimana ketiga puisi di atas diterjemahkan melalui perspektif metode penerjemahan Newmark. Penelitian ini menggunakan metode kualitatif. Analisis menunjukkan bahwa “Antara Kita” atas Between Us dan “Nyanyian Duniawi” atas A Worldly Song yang diterjemahkan oleh Harry Aveling didominasi oleh metode free translation dan diksi yang terdapat di dalam teks sumber dan terjemahan tidak dapat digolongkan ke dalam teks pornografi. Simpulan yang diperoleh adalah erotisme di kedua puisi itu dihadapkan pada pemilihan diksi sehingga tidak termasuk ke dalam pornografi yang begitu verbal dan cabul. Erotisme di kedua puisi di atas mencerminkan adanya hasrat dari dua subjek yang saling menginginkan cinta dan tubuh mereka.